Position sensitive detectors in proton therapy: online monitoring of the beam position. (1st October 2022) - Schaefer, R.; Actis, O.; Koenig, S.; Eichin, M.; Weber, D.C.
Abstract: Spot-scanning is a highly dynamic treatment method in proton therapy, tailored to each tumor shape individually. By superimposing many single spots in all three spatial axes, a prescribed dose is applied to the tumor volume. To minimize dose inhomogeneity across this volume, tight constraints on the beam position accuracy apply: for a dose inhomogeneity below 1%, a longitudinal beam position accuracy of the order of 1 mm is necessary, whereas in the lateral plane, the accuracy needs to be roughly one order of magnitude better. Longitudinal position control is achieved through selecting the beam energy; laterally, this is achieved by two sweeper magnets, allowing position changes within milliseconds. Such dynamics and accuracy constraints require an online measurement of the beam position to enable and maintain high treatment quality assurance. Gantry 2 at the Center for Proton Therapy at PSI operates a plane parallel strip ionization chamber for this purpose as the final beamline element before the patient. The foil-based detector design is optimized for an in-situ placement in the beam axis and keeps beam disturbance at a minimum. A strip pitch of 2 mm allows to reconstruct the Gaussian shape beam profile with the desired accuracy. These beam profiles are analyzed (and verified) during a treatment on a spot-by-spot basis, before the next spot is applied, introducing a dead time after every spot. Applying 50, 000 spots in a treatment introduces the challenge to data acquisition and — processing in terms of keeping treatment times reasonable. Data pileup and long dead times are mitigated by optimized front-end electronics and early-stage data processing, without compromising data quality and the accuracy of the measured beam position.